Immunodiagnosis of Besnoitia besnoiti infection by ELISA and Western blot - Cortes, H.C.E. (2012)
Abstract Besnoitia besnoiti, an obligate intracellular apicomplexan protozoan parasite, is the causative agent of bovine besnoitiosis. This infection may dramatically affect body condition and lead to irreversible infertility in males, resulting in important economical losses in livestock production. Identification of serologically positive animals is of major relevance to elaborate appropriate measures of control. While identification of clinical cases is relatively easy to carry out, the finding of subclinical forms of infection is more difficult, thus serology is considered as an appropriate diagnostic tool. In view to improve and validate immunodiagnosis, we evaluated an enzyme-linked immunosorbent assay (ELISA), complemented with a Western blot (both using a somatic B. besnoiti-tachyzoite antigen) to detect anti-B. besnoiti antibodies in bovine sera. The comparative evaluation of the 2 methods, using 13 sera from animals affected by the chronic phase of besnoitiosis and 10 asymptomatic carriers, yielded a diagnostic sensitivity of 87% for ELISA and 91% for Western blot analyses. Specificity was tested with sera from animals with confirmed Toxoplasma gondii (n = 5) and Neospora caninum (n = 12) infection, and with 64 negative sera from either an endemic or a non-endemic area. The ELISA specificity ranged between 96.4% and 98%, the Western blot specificity between 96.4% and 100%. The present study demonstrated that ELISA and Western blot, using in vitro generated somatic B. besnoiti antigen, is a useful tool combination to reliably detect animals that have been exposed to B. besnoiti infection, including both asymptomatic and symptomatic courses of disease.